Aplicación de Lean construction al sector de la infraestructura vial en Colombia (2018)
The construction in the sector of road infrastructure in Colombia is still characterized by being traditionalist when executing and controlling the operational and administrative activities of the projects, this is why the construction companies of our country present serious difficulties for the identification of activities that do not add value and that on the contrary generate reprocesses and losses for companies in their projects. The conventional work system does not allow to identify the possible causes by which the problems of efficiency and effectiveness in the processes are generated and on the contrary, it is difficult to take corrective actions on them, presenting problems in the increase of the productivity, affectations in the quality which would translate into economic losses for companies and / or projects.